2013
DOI: 10.1103/physrevb.87.140302
|View full text |Cite
|
Sign up to set email alerts
|

Minimum thermal conductivity in superlattices: A first-principles formalism

Abstract: The thermal conductivity of silicon-germanium superlattices is computed from density-functional perturbation theory using relaxation times that include both anharmonic and interface roughness effects. A decrease in the group velocity of low-frequency phonons in addition to the interface-disorder-induced scattering of high-frequency phonons drives the superlattice thermal conductivity to below the alloy limit. At short periods, interplay between decrease in group velocity and increase in phonon lifetimes with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 37 publications
9
102
1
2
Order By: Relevance
“…In comparable superlattices with well-defined periodic interfaces, phonon coherence is important only for sub-10 nm periods at 300 K, whereas diffusive phonon scattering by interfaces is dominant for larger periods. 29,30 Consistently, more recent analysis shows that diffusive pore-edge phonon scattering is sufficient to explain the data of nanoporous films with feature sizes larger than 100 nm at 300 K. 31 As the second mechanism, pore-edge amorphization and oxidation, as found in real Si thin films, 8 may largely affect k L for fine nanoporous structures. 1 Such amorphous and surface oxidation layers usually have a few nm thickness.…”
Section: Introductionsupporting
confidence: 55%
“…In comparable superlattices with well-defined periodic interfaces, phonon coherence is important only for sub-10 nm periods at 300 K, whereas diffusive phonon scattering by interfaces is dominant for larger periods. 29,30 Consistently, more recent analysis shows that diffusive pore-edge phonon scattering is sufficient to explain the data of nanoporous films with feature sizes larger than 100 nm at 300 K. 31 As the second mechanism, pore-edge amorphization and oxidation, as found in real Si thin films, 8 may largely affect k L for fine nanoporous structures. 1 Such amorphous and surface oxidation layers usually have a few nm thickness.…”
Section: Introductionsupporting
confidence: 55%
“…The crossover from a coherent to incoherent regime is naturally included in our formulation. We thus observe the minimum thermal conductivity of superlattices [12,18,20] under the atomistic Green's function framework.…”
Section: Resultsmentioning
confidence: 99%
“…Lattice dynamics based on damped wave functions was used to predict a minimum in the thermal conductivity * Corresponding author: gchen2@mit.edu of superlattices in the cross-plane direction [17,18]. More recently, a perturbation method based on the Fermi golden rule [11,19,20] was developed, but the method may have limitations on treating interface scattering, as strong scattering may not be captured by perturbation. One alternative approach is to use molecular dynamics simulations [21,22], which do not assume the nature of phonon transport but are classical in nature.…”
Section: Introductionmentioning
confidence: 99%
“…115 Several studies documented the optimal sizes and distributions in the nanocomposites. [116][117][118][119] Mingo et al studied 17 different silicide nanoparticles in the SiGe host, 116 and revealed the existence of the optimal nanoparticle size that minimises the nanocomposite's κ L . Similarly, the optimal Si/Ge superlattice period of around 3.3 nm minimised the value of the κ L .…”
Section: From the Conventional Phonon-phonon Interactions To Nanostrumentioning
confidence: 99%
“…Similarly, the optimal Si/Ge superlattice period of around 3.3 nm minimised the value of the κ L . 117 Besides the focus on κ L , calculations were also made to estimate ZT values for some composite systems such as SiGe composites, nanotubes and quantum dot superlattices. [120][121][122] A great progress has been achieved in reducing the κ L by scattering phonons over a wide range of frequencies.…”
Section: From the Conventional Phonon-phonon Interactions To Nanostrumentioning
confidence: 99%